Pricing High-Tech Company by Real Options Approach: A Case Study of HTC - tsai, shunhui (2007)
Traditionally, Discounting Cash Flows (DCF) approaches are used to project valuation and then extend to company valuation. With the uprising development of options theory and computational techniques, an alternative valuation approach - real options approach is proposed to emphasize what traditional valuation approaches neglect. Since high-tech companies have option-like characteristics and asymmetric payoffs, this paper attempts to apply real options pricing model developed by Schwartz and Moon (2000, 2001) to price high-tech companies and look for the key value drivers. The paper adopts case study methodology, focusing on a leading company --High Tech Computer (HTC), which is develops and produces Smart phones and Pocket PCs. After simulations, it seems this model can produce a reasonable result for valuation purpose.